2021
DOI: 10.1007/s10147-021-01929-5
|View full text |Cite
|
Sign up to set email alerts
|

Current trend in treatment of glioblastoma in Japan: a national survey using the diagnostic procedure combination database (J-ASPECT study-glioblastoma)

Abstract: Background In the treatment for glioblastoma (GBM), treatment modalities, such as bevacizumab (BEV) and carmustine wafers implants have been approved in Japan since 2013. However, it is unclear whether such a trend in treatment complexity can accelerate treatment centralization. The aim of this study was to reveal the current trend in the treatment of GBM in Japan. Methods We used diagnostic procedure combination (DPC) database to analyze the data of 1,774… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Thereafter, Japanese institutes, including ours, have launched several real-world studies, which indicate the clinical benefits of optional first-line BEV for patients with severe clinical conditions [1,[6][7][8][9][10]. Practically, we selected first-line BEV for patients with unresectable GBM and accumulated the clinical data [11]. These case series revealed that the radiographic course following first-line BEV for unresectable tumors varied among patients, and its outcome was considered an unresolved issue that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Japanese institutes, including ours, have launched several real-world studies, which indicate the clinical benefits of optional first-line BEV for patients with severe clinical conditions [1,[6][7][8][9][10]. Practically, we selected first-line BEV for patients with unresectable GBM and accumulated the clinical data [11]. These case series revealed that the radiographic course following first-line BEV for unresectable tumors varied among patients, and its outcome was considered an unresolved issue that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, Japanese institutes, including ours, have launched several real-world studies, which indicate the clinical bene ts of optional rst-line BEV for patients with severe clinical conditions [1,[6][7][8][9][10]. Practically, we selected rst-line BEV for patients with unresectable GBM and accumulated the clinical data [11]. These case series revealed that the radiographic course following rst-line BEV for unresectable tumors varied among patients, and its outcome was considered an unresolved issue that needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%